2018
DOI: 10.5897/ajb2018.16452
|View full text |Cite
|
Sign up to set email alerts
|

Efficient plant regeneration protocol for finger millet [Eleusine coracana (L.) Gaertn.] via somatic embryogenesis

Abstract: In the present study, an efficient protocol for somatic embryogenesis and plant regeneration was established in six finger millet varieties (GBK-043137, GBK-043128, GBK-043124, GBK-043122, GBK-043094 and GBK-043050). Shoot tips from 3 days in vitro grown plants were inoculated on MS supplemented with various concentrations and combinations of α-naphthaleneacetic acid (NAA), 2,4-Dichlorophenoxyacetic acid (2,4-D), benzylaminopurine (BAP) and kinetin for callus induction and somatic embryogenesis. For shoot rege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Eapen and George (1989) reported the first finger millet plant regeneration through somatic embryogenesis. Several studies reported the use of somatic embryogenesis in finger millet (Eapen & George, 1989; Ngetich et al, 2018; Venkatesan et al, 2022), using embryoids for genetic engineering. There are successful finger millet plant regeneration using organogenesis (Mukami et al, 2018; Kansara et al, 2023.)…”
Section: Genetic Engineering and Genome Editingmentioning
confidence: 99%
“…Eapen and George (1989) reported the first finger millet plant regeneration through somatic embryogenesis. Several studies reported the use of somatic embryogenesis in finger millet (Eapen & George, 1989; Ngetich et al, 2018; Venkatesan et al, 2022), using embryoids for genetic engineering. There are successful finger millet plant regeneration using organogenesis (Mukami et al, 2018; Kansara et al, 2023.)…”
Section: Genetic Engineering and Genome Editingmentioning
confidence: 99%
“…Previous studies on finger millet have identified several inherent challenges associated with in vitro regeneration, such as the severe recalcitrant nature, polyploidy, and genotypic dependence, which singly or collectively frustrate the plant tissue culture work and, consecutively, the crop improvement systems through transgenesis (Dosad and Chawla, 2016). Plant regeneration in finger millet using different explants in different genotypes has been reported, such as epicotyl (Patil et al, 2009), shoot apical meristem (Babu et al, 2018;Ngetich et al, 2018), mature seeds (Bayer et al, 2014;Pande et al, 2015), and mature embryos (Satish et al, 2016). These protocols provide an opportunity to improve in vitro plant regeneration studies in finger millet, although optimization is required for each genotype.…”
Section: Transgenesis For Blast Resistancementioning
confidence: 99%